Citizenship termination of the Republic of Kazakhstan (legal regulation issues) - Turlayev, A.V.; Ybyray, A.K. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article illustrates problematic legal regulation issues and formalizes the termination of Kazakh citizenship practice and its registration in a loss case. Citizenship termination is considered a continuing legal relationship, which has stages, conditions, and legal regulation in the law and by-laws. The features analysis of the citizenship termination in the legislation of the Republic of Kazakhstan and foreign countries was carried out. The research purpose is a comprehensive analysis of the theory and Kazakh citizenship termination practice, the problems identification in the termination registration process of citizenship, and the ways development to solve them. The research is carried out by general scientific and special legal methods; analysis and generalization of theoretical provisions and legal norms, and implementation practice are used. Citizenship cessation is regarded as a continuing legal relationship. Based on the comparative legal method, the main trends in the development of the legal institution “citizenship termination” at present is revealed. The research goal is the provision on the need to improve the institution of “citizenship termination” in the law and by-laws. In conclusion, it is proposed to correct the legal norms of the Law “On Citizenship”, addenda to by-laws regulating Kazakh citizenship termination to simplify and streamline the procedure for citizenship termination.
Прекращение гражданства Республики Казахстан (проблемы правовой регламентации)
Қазақстан Республикасының азаматтығын тоқтату (құқықтық реттеу мəселелері)
Keywords: citizenship; mono-citizenship; legislation on citizenship; citizenship termination; citizenship loss; second citizenship